Exploring Quantitative and Qualitative Methodologies: A Guide to Novice Nursing Researchers - Salvador, Jordan Tovera (European Scientific Journal, ESJ, 2016)
This paper reviews three research articles concerning the methodologies of quantitative and qualitative research. The body of knowledge can be used as a guide for novice researchers who wanted to have in-depth understanding about the nature and underpinnings of each research design. The first article written by Beverly Hancock, ‘Trent for Research and Development in Primary Care: An Introduction to Qualitative Research (2002)’, emphases on the foundations of qualitative research in application to primary health care setting; the second article authored by Gary Rolfe, ‘Validity, Trustworthiness, and Rigor: Quality and the Idea of Qualitative Research’ (2006), accentuates the methodological `issues in nursing research; and the last article written by Looi Theam Choy, ‘The Strengths and Weaknesses of Research Methodology: Comparison and Complimentary between Qualitative and Quantitative Approaches’ (2014), spotlights the similarities and differences of both research methodologies in the field of social sciences. Fundamentally, it would specify a necessary knowledge, adequate information, and appropriateness in the applicability of the research design. Likewise, it would stipulate a realization for the readers about the coexistence of both research approaches in any field of investigation.